TINJAUAN HUKUM ISLAM TERHADAP TRADISI JUJURAN PERKAWINAN DALAM ADAT SUKU DAYAK NGAJU (Studi Kasus Desa Manjalin Kecamatan Parenggean Kabupaten Kotawaringin Timur) - M.Ridwan; Masrokhin Masrokhin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to determine the Islamic legal perspective on the tradition of "jujuran" in the customs of the Ngaju Dayak Tribe in Manjalin Village. This type of research is normative law, using the Historical Approach and Conceptual Approach. Data collection was done through interviews with research subjects, observations by the researcher directly on the research object. After gathering the information, the next step is to analyze the data. In this writing, the researcher uses descriptive analysis to analyze how Islamic law views the tradition of "jujuran" in the Ngaju Dayak customs. The research concludes that the Ngaju Dayak community in Manjalin Village considers giving "jujuran" to be mandatory for the prospective bride from the groom's side. "Jujuran" is a gift from the groom to the bride in the form of a certain amount of money determined by the bride. "Jujuran" is different from "mahar" because usually "jujuran" has a higher value. The function of "jujuran" is to assist in the implementation of the wedding reception and also as initial capital to start a household. However, sometimes in the payment of "jujuran," the demands from the bride's side can be too high, hindering the marriage process, which is not in line with Islamic teachings. On the other hand, there are also those who determine "jujuran" through deliberation to reach an agreement, in accordance with Islamic teachings.